PATTERNS OF DEMENTIA IN PARKINSON'S DISEASE PATIENTS (The Research of Medical Science Review, 2025)
Background: The bioimpedance spectroscopy shows promise as a tool for surveillance of Parkinson’s Disease (PD) and Dementia with Lewy Bodies (DLB), neurodegenerative disorders, for which Lewy bodies are observed. Both conditions have pathological features in common, but their clinical manifestations differ significantly, particularly in terms of dementia. This is important to know when and how to make a diagnosis, how to treat the disease, and how to improve patient outcomes.Objective: The purpose of this study is to determine how incidence and patterns of dementia differ in PDD and DLB patients with amnestic and non-amnestic subtypes of dementia.Methods: A six-month cross-sectional study was done at the Department of Neurology, Sheikh Zayed Hospital, Lahore. By consecutive sampling, a total of 70 PD patients above 55 years were recruited. The Montreal Cognitive Assessment (MoCA) was used to assess dementia as well as clinical assessments. Since Nicoletti et al. [1] estimated 4.8% prevalence of PDD, we calculated the sample size. Descriptive statistics, data analyses with SPSS version 26 (chi square test) and logistic regression were used to test significant associations and predictors from the data.Results: Of the 70 PD patients, 40 percent had evidence of dementia, with amnestic dementia (60 percent) and non-amnestic multidomain dementia (30 percent) most and executive dysfunction (10 percent). Older age, longer disease duration, and higher incidence of motor symptoms were significantly associated with the incidence of dementia (p < 0.05). In PD patients, age over 60 years (OR=2.5, p=0.01), duration over five years (OR=3.0, p=0.01) and advanced motor symptoms (Hoehn and Yahr Stage III-IV; OR=4.0, p<0.001) were independently found to be associated with dementia.Conclusion: PD patients have a high prevalence for dementia, most commonly amnestic. PD dementia is also predicted by age, disease duration and motor symptom severity. Establishing early identification and management of cognitive impairments improves patient outcomes and their quality of life. Since causality relationships and progression of dementia in PD remain yet to be elucidated, future longitudinal studies with larger cohorts are needed to further clarify their association.